Impact of surgical approach on progress of disease by type of histology in stage IA endometrial cancer: a matched-pair analysis - Huixian Miao; Lin Zhang; Yi Jiang; Yicong Wan; Lin Yuan; Wenjun Cheng (BMC Surgery, 2024)
Abstract Background To compare the impact of surgical approach on progression free survival (PFS) stratified by histologic type in women diagnosed with stage IA endometrial cancer. Methods Myometrial invasion is classified into no myometrial invasion, <50% and ≥50%, with only no myometrial invasion and <50% are included in stage IA patients. A retrospective study is designed by collecting data from women diagnosed as stage IA endometrial cancer from January 2010 to December 2019 in a tertiary hospital. A propensity score is conducted for 1:1 matching in the low-risk histologic patients. Progression free survival and disease-specific survival data are evaluated by the Kaplan–Meier method and compared by the log-rank test in both the whole population and the matched-pair groups. A sub-group analysis is performed to figure out risk factors associated with the effect of surgical approach on PFS and disease-specific survival (DSS). Results 534 (84.49%) low-risk histologic endometrial cancer women, with 389 (72.85%) operated by minimally invasive surgery and 145 (27.15%) by open approach, and 98 (15.51%) high-risk histology, with 71 (72.45%) by laparoscopy and 27 (27.55%) by open surgery, are included. Compared to open surgery, laparoscopy results in lower progression free survival in low-risk patients before and after matching (p = 0.039 and p = 0.033, respectively), but shows no difference in high-risk patients (p = 0.519). Myometrial invasion is associated with lower progression free survival in laparoscopy in low-risk histology (p = 0.027). Conclusion Surgical approaches influence progression free survival in stage IA low-risk histologic diseases, especially in those with myometrial invasion, but not in high-risk histologic endometrial cancer.